Monitoring Baby Incubator Central Based Raspberry Pi Zero W with Temperature and Skin Temperature Parameter Based on IoT - Ningsih, Fransiska Ima Setia; Irianto, Bambang Guruh; Lamidi , Lamidi; Abdulhamid, Mohanad (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
This research is dedicated to enhancing the quality of care provided to vulnerable infants by proactively addressing potential challenges. The goal is to recreate the optimal environmental conditions resembling the mother's womb—ensuring precise maintenance of temperature, humidity, and oxygen levels—through the utilization of infant incubators. The primary objective of this study revolves around the development of an autonomous monitoring tool tailored for midwives and healthcare personnel responsible for overseeing multiple infant incubators. Driven by the synergy of an ESP32 module and Raspberry Pi Zero W, this innovative tool seamlessly transfers crucial data through the vast network of the Internet of Things (IoT). The acquired results are meticulously compared against data obtained from an incubator analyzer, employing a meticulously designed pre- and post-experimental framework. Examination of the chamber temperature measurement data brings to light a maximum error threshold of 0.009%, corresponding to an error value of 3. Notwithstanding certain persisting measurement discrepancies within the developed module, the study's profound utility is projected to significantly aid medical professionals in their concurrent monitoring of multiple infant incubators, thereby mitigating the impact of these limitations and advancing the realm of neonatal care.